USING THE INTERNATIONAL SCIENTOMETRIC DATABASES OF OPEN ACCESS IN SCIENTIFIC RESEARCH - Galchevska, О.А. (Journal of Information Technologies in Education (ITE), 2015)
In the article the problem of the use of international scientometric databases in research activities as web-oriented resources and services that are the means of publication and dissemination of research results is considered. Selection criteria of scientometric platforms of open access in conducting scientific researches (coverage Ukrainian scientific periodicals and publications, data accuracy, general characteristics of international scientometrics database, technical, functional characteristics) and their indexes are emphasized. The review of the most popular scientometric databases of open access Google Scholar,Russian Scientific Citation Index (RSCI), Scholarometer, Index Copernicus (IC), Microsoft Academic Search is made. Advantages of usage of International Scientometrics database Google Scholar in conducting scientific researches and prospects of research that are in the separation of cloud information and analytical services of the system are determined.